Individual Character: Towards Empirical Investigation - Weragoda, R.B.L.; Opatha, H.H.D.N.P. (Canadian Center of Science and Education, 2016)
Attached

T h e stu d y o f in d iv id u a l c h a r a c te r is an e s s e n tia l a r e a fo r o r g a n iz a tio n a l r e s e a r c h a s it is in str u m e n ta l in e n s u r in g e th ic a l b e h a v io r at in d iv id u a l an d o r g a n iz a tio n le v e l. H o w e v e r it is o b s e r v e d in th e lite ra tu re th a t th is a r e a h a s b e e n la r g e ly u n ta p p ed an d e s p e c ia lly m o r a l a n d s o c ia l d im e n s io n s o f c h a r a c te r h a v e b e e n ig n o r e d in c o n te m p o r a r y s tu d ie s . F u rth er, it is o b s e r v e d th at c h a r a cte r a n d r e la te d te r m s, i.e . v ir tu e s , m o r a lity , e th o s a n d v a lu e s h a v e b e e n w id e ly u se d in te r c h a n g e a b ly d u e to c o n c e p tu a l a m b ig u ity (th e o n to lo g ic a l b a s is ) an d c e r ta in in str u m e n ts u s e d fo r e m p ir ic a l in v e s tig a tio n s p o te n tia lly s u ffe r d u e t o m e th o d o lo g ic a l a m b ig u ity (th e e p is t e m o lo g ic a l b a s is ) o f th e c o n str u c t. In th is p ap er, w e h a v e fo r m u la te d a c o n c e p tu a lly so u n d d e fin itio n w h ic h p r o v id e s a c le a r d ir e c tio n fo r fu tu re e m p ir ic a l in v e s tig a tio n s a n d fa c ilita te s t o d iffe r e n tia te in d iv id u a l c h a r a cte r fr o m o th e r r e la te d te r m s . F in a lly , w e p r o p o s e c er ta in m is s in g a n d n e w d im e n s io n s o f in d iv id u a l c h a r a c te r a n d r e c o m m e n d p r o m is in g r e s e a r c h d ir e c tio n s in or d e r to further e x p a n d c o n te n t v a lid ity o f th e c o n str u c t
Keywords: character; character strength; ethos; morality; virtues